PENGARUH POLA ASUH OTORITER ORANGTUA TERHADAP PERILAKU MORAL ANAK DI RW 2 KELURAHAN TUAN-TUAN - Rahmah, Annisa; Ulfah, Maria; Hari C, Ludovicus Manditya (Universitas Tanjungpura, 2023)
The purpose of this study was to analyze (1) the authoritarian parenting style of parents in Rw 2 Tuan-tuan Village, (2) the moral behavior of children in Rw 2 Tuan-tuan Village, and (3) the influence of authoritarian parenting parents in Rw 2 Tuan-tuan Village. The method used in this study is a quantitative with survey-based approach.This study used a population of 72 respondents, namely authoritarian parents in Rw 2 Tuan-tuan Village, Benua Kayong District, Regency. The technique used in data collection was using a Likert scale questionnaire which was distributed directly to the respondents. Data analysis in this study used simple linear regression analysis assisted by the IBM SPSS 26 application with the results showing that: (1) the authoritarian parenting style of parents in Tuan-tuan Village Rw 2 has an interpretation score of 80.07%, placing it in the high category, (2) the moral behavior of children in Tuan-tuan Village Rw2 Ketapang Regency is included in the high category with an interpretation score of 80.26%, (3) there is an influence of authoritarian parenting styles on children's moral behavior as indicated by sig.alpha 0.000 0.005 and a coefficient of determination of 0.790 or 79%.